GOLPUT DAN PEMILU 2024 - maringan panjaitan; Jonson Rajagukguk; Grace Y Damanik; Elfrida Aruan; Rahmat Syukur Gulo (Jurnal Ilmu Sosial Dan Politik, 2022)
General elections are a means of upholding people's justice and this is the only process to build a country's political ethics. In elections, citizens are given as much freedom as possible and guaranteed by the constitution to express their political aspirations. Through elections, citizens will come to the polls and have been regulated by the state through special regulations regarding general elections. Citizens will give their political rights so that in the future a government structure will be created that will organize state governance for public services and accelerate development. The problem is, is an election valid if the citizen's participation is minimal or far from what we expect? Like the term white group (abstentions) where citizens are very passive and do not give their political rights. We will enter the political year and the 2024 elections are getting closer. Can the abstentions increase or decrease? This is certainly a very relevant question so that the legality of elections can be better because every citizen's political election participation is a supporting factor for the success of elections.